Severe thrombosis of bioprosthesis mitral valve after dabigatran - Çağdaş Akgüllü; Ufuk Eryılmaz; Tünay Kurtoğlu (KARE Publishing, 2013)
A 41-year-old female was admitted to our hospital with an unidentified source of fever, dyspnea and dizziness. Transthoracic echocardiography demonstrated severe mitral valve regurgitation, and further examination with transesophageal echocardiography (TEE) revealed a 7 mm vegetation on the anterior mitral leaflet. Blood cultures were negative, and after 45 days of empiric 12 g/day ampicillin-sulbactam therapy, the vegetation was shown to have disappeared. However, due to ongoing severe mitral regurgitation and valve deformity, a prosthetic metallic mitral valve replacement was performed. After the operation, TEE was performed again due to subfebrile fever; however, the valve was normal and blood cultures were negative. Because of the probable relapse risk of infective endocarditis, the preoperative intravenous antibiotherapy was continued for 21 days and then orally for one week. Then, she was placed on follow-up by our outpatient clinic. As her INR was highly unstable during this period and she developed newonset subfebrile fever, she was hospitalized again, and the TEE demonstrated vegetation. Blood cultures were still negative, and a combination of vancomycin-rifampicin-gentamicin was started. While under that therapy, first stroke and after a few days recurrent trans-ischemic attack developed, and the vegetation was seen to have enlarged. Urgent valve operation was performed with a bioprosthetic mitral valve, and ampicillinsulbactam therapy was added to her previous antibiotherapy at the suggestion of the Microbiology Department. Oral anticoagulant therapy was planned for three months; however, during the postoperative period, her INR levels were highly unstable and could not be maintained in therapeutic ranges for even two consecutive days. Adjusted dosage of dabigatran to 110 mg/bid according to renal clearance in combination with 150 mg/day aspirin was started. However, valve thrombosis and a massive stroke developed under this therapy. The thrombosis disappeared after continuous heparin infusion, and she was discharged with neurological sequelae on 150 mg/day aspirin 55 days after her last operation. During the follow-up period of four months, no other clinical events occurred.